Techno-economic and environmental assessment of floating solar power with innovative charging systems for decarbonizing maritime operations in the UK - Qin, Qing; Adeboye, Lukman; Ibrahim, Khalifa Aliyu; Luk, Patrick Chi-Kwong; Xie, Ying; Verdin, Patrick G.; Luo, Zhenhua; Huang, Luofeng (Elsevier, 2026)
Maritime transportation contributes around 3 % of global emissions. As global trade and manufacturing expand, the decarbonization of maritime operations becomes an urgent challenge. Ferry ports in the UK face significant barriers to energy transition, including limited grid capacity, lack of charging infrastructure, and constrained land availability. This study proposes the development of a Floating Photovoltaic (FPV) plant on the sea near the port to independently generate renewable electricity for charging electric vessels operating between UK and France. Four scenarios are analyzed, varying in energy generation targets and ground coverage ratios (GCRs). Energy performance is evaluated using the System Advisor Model (SAM), estimating electricity generation and battery energy storage system (BESS) requirements under limited solar irradiance. A comprehensive economic analysis examines capital expenditure (CAPEX), operational expenditure (OPEX), levelized cost of energy (LCOE), revenue, and payback periods. The study also assesses environmental benefits by quantifying CO2 emissions for FPV lifespan and compares them to diesel-based energy. Moreover, charging technologies are reviewed in relation to current technologies, and a logistics plan for integrating FPV systems and electric vessels is proposed. Results demonstrate that the FPV plant can minimize BESS requirements, and reduce payback periods to as little as 3.62 years, facilitating the pathway of ferry ports to achieve net-zero emissions by 2045, with an estimated reduction of 17million tonnes of CO2 annually. This study is among the first to assess the feasibility of using FPV systems to charge electric vessels at a UK marine port, integrating real-world spatial constraints, phased deployment planning, and life-cycle environmental analysis. It also introduces the conceptual integration of floating wireless charging infrastructure, offering a forward-looking approach to maritime electrification.
Keywords: Techno-economic-environmental assessment; Floating solar; Logistics plan; Maritime decarbonization; System advisor model; Levelized costs of energy; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Energy